(3eTjNI GHf CfLH GdHZOGOis - (3eMeO GdGfLH Hf CHh YHO Gddg Hf YHO GdQMef GdUhaj GdHZOGOj, VjGA GdOjf CHh GdMSf,J (B674 (3g` s ((3SHW GHf MLQ s)
(3ChdgG (B:s
(3GdMeO ddg LGeY GdTJGJ heNQL GdfHGJ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B146 - (3U(B179s
(3GdeDda ai HQhcdeGf edMb (B1/590 (3JGL GdOjf Ydi Hf CfLH Hf GdSGYi GdHZOGOi hde jPcQ GdeTjNI Hjf cJHgs
(3gPg GdfSNI YdjgG SeGYGJ hbQGAGJ cKjQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B249 s
(3eUOQ GbJfGA GdCUd (B:s
(3chHQjdi (B(14/1584) s
Keywords: (3GdJGQjNs